2022
DOI: 10.21037/atm-22-3545
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA TERC promotes gastric cancer cell proliferation, migration, and invasion by sponging miR-423-5p to regulate SOX12 expression

Abstract: Background: Long non-coding RNAs (lncRNAs) play critical roles in gastric cancer (GC) initiation progression. However, the biological function of the lncRNA telomerase RNA component (TERC) remains unknown in human GC. The present study sought to determine the biological function and underlying molecular mechanism of the lncRNA TERC in GC progression. Methods:The expression levels of the lncRNA TERC in GC tissues and cell lines were analyzed using reverse transcription-quantitative polymerase chain reaction (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
1
0
1
Order By: Relevance
“…The LncSEA analysis revealed that TERC was hypermethylated (Figure 4G) and that it interacts with several miRNAs, especially tumour-suppressive miRNAs (Figure 4A). Although this study is the first to report TERC hypermethylation and sponging of the tumour-suppressor miRNA-320 family in PCa, similar TERC oncogenic mechanisms have been reported in gastric cancer, where TERC was shown to sponge miR-423-5p, thus promoting the proliferation of gastric cancer [42]. TERC upregulation in PC-3 cells is further supported by RNA-sequencing data, where in normal prostate epithelia, its expression is −16.61 [43].…”
Section: Discussionsupporting
confidence: 77%
“…The LncSEA analysis revealed that TERC was hypermethylated (Figure 4G) and that it interacts with several miRNAs, especially tumour-suppressive miRNAs (Figure 4A). Although this study is the first to report TERC hypermethylation and sponging of the tumour-suppressor miRNA-320 family in PCa, similar TERC oncogenic mechanisms have been reported in gastric cancer, where TERC was shown to sponge miR-423-5p, thus promoting the proliferation of gastric cancer [42]. TERC upregulation in PC-3 cells is further supported by RNA-sequencing data, where in normal prostate epithelia, its expression is −16.61 [43].…”
Section: Discussionsupporting
confidence: 77%
“…TERC (telomerase RNA component) serves as a template for telomere replication catalyzed by the telomerase enzyme, which contributes to the uncontrolled proliferation of cancer cells. Despite the fact that our experimental data were not confirmed by the data of the GEPIA database for breast cancer, an increase in TERC expression was shown for gastric cancer [17], and TERC was proposed as a diagnostic marker in cervical cancer [18] and lung cancer [19]. MEG3 (maternally expressed 3) is a relatively well-studied lncRNA demonstrating oncosuppressive properties.…”
Section: Resultscontrasting
confidence: 58%